Meta-Analysis of Scientific Papers in the Field of Motor Skills from Volleyball Published in the Journal Sport Mont 2006-2016 - Gorica Zoric (Journal of Anthropology of Sport and Physical Education, 2018)
The main goal of this research was to determine one meta analysis of published original scientifi c papers in the area of motor abilities in volleyball in Sport Mont Journal in 2006-2016. From the review of the published original scientifi c papers that are being analyzed, it can be seen that this is a longitudinal research. In this paper, a meta analysis of 6 papers in the fi eld of motor skills in volleyball was conducted. Analyzing the basic central and dispersion parameters in all original scientifi c papers in the fi nal state, it was noticeable that the arithmetic meanings had better values in almost all values compared to the initial state. To determine the statistical signifi cance for evaluating diff erent tests in published works, t-test for dependent samples and multivariate analysis of MANOVA were applied. T-test values and multivariate analyzes were signifi cant or signifi cance level (Sig.) from 0.01 (p≤.01) in almost all variables. This systematic overview shows a comparative analysis of the collected studies and the processed data. It can be concluded that the training program of all scientifi c orginal papers has led to positive transformations.